Mixtures of heavy fuel oil and green hydrogen in combustion equipment: Energy analysis, emission estimates, and economic prospects - Carvalho, Felipe S.; Lacava, Pedro T.; Rufino, Caio H.; Travieso Pedroso, Daniel; Blanco Machin, Einara; H. M. Araújo, Fernando [UNESP]; Gómez Acosta, Daviel; Carvalho Jr., João A. [UNESP] (Elsevier, 2023)
The high environmental impact of fossil fuels combined with the rise of carbon dioxide in the atmosphere has made the search for renewable fuels imperative. The study assesses the technical and economic viability of replacing heavy fuel oil (HFO) with green hydrogen (H2) in industrial plants for high temperature generation (>1100 K). The study also estimates the emissions generated by the plants after the fuel switch in terms of particulate matter (PM), SO2, NOx and CO2 emissions. To illustrate the feasibility of this replacement, an assessment of a calcination furnace at a pulp plant in Chile in 2022 was carried out, taking into account two electricity generation scenarios for H2 production by water electrolysis. Replacing HFO with a mixture of H2 + HFO was beneficial in terms of emissions. The financial assessment showed that blending H2 with HFO of up to 20 % is the best solution, considering current fuel prices, and that full substitution of HFO with H2 after 2030 is economically viable.
Keywords: Fuel blends effects on emissions; Fuel blends forecast prices; Fuel oil replacement; Hydrogen in industrial equipment